A Prospective, Comparative Study on Robotic Versus Open-Surgery Hysterectomy and Pelvic Lymphadenectomy for Endometrial Carcinoma. Issue 2 (February 2015) - Eklind, Saskia; Lindfors, Anna; Sjöli, Per; Dahm-Kähler, Pernilla
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to compare surgical outcome, patient recovery, and costs between robot-assisted laparoscopy and laparotomy in women undergoing hysterectomy, bilateral salpingo-oophorectomy (BSOE), and pelvic lymphadenectomy for endometrial carcinoma. Methods Women undergoing hysterectomy, BSOE, and pelvic lymphadenectomy for endometrial carcinoma, according to regional guidelines, were prospectively, concurrently, and consecutively included from September 2010 to December 2012. Surgical outcomes such as operative time, estimated blood loss (EBL), number of lymph nodes retrieved, and complications were analyzed together with hospital stay, days until normal active daily living was retrieved, patient satisfaction with the length of the hospital stay, and cost per patient. Robot-assisted laparoscopy was performed on all cases at the Sahlgrenska University Hospital, and laparotomy was performed on all cases at 3 regional hospitals. Results Forty women underwent robot-assisted laparoscopy, and 48 underwent laparotomy. There were no differences in age, body mass index, histology, or retrieved lymph nodes. Operative time was significantly shorter in the robot-assisted laparoscopy group (P < 0.0001). The EBL was lower and hospital stay was shorter in the robot-assisted laparoscopy group (P < 0.0001). There was no statistical difference in complications between the groups, and both groups found hospital stay duration satisfactory. In the robot-assisted laparoscopy group, active daily living was normal within 5 days postoperatively, compared with 14 days in the laparotomy group (P < 0.0001). Calculated costs per treated patient did not differ statistically between the groups. Conclusions Compared with laparotomy and robot-assisted laparoscopic hysterectomy, BSOE pelvic lymphadenectomy for endometrial carcinoma was associated with significantly shorter operative time, hospital stay, and lower EBL. Patients recovered more quickly after robot-assisted laparoscopy, with equal costs number of retrieved lymph nodes, compared with laparotomy.